Bright x-ray radiation from plasma bubbles in an evolving laser wakefield accelerator - Mangles,S (Physical Review Accelerators and Beams, 2020)
We show that the properties of the electron beam and bright x rays produced by a laser wakefield accelerator can be predicted if the distance over which the laser self-focuses and compresses prior to self-injection is taken into account. A model based on oscillations of the beam inside a plasma bubble shows that performance is optimized when the plasma length is matched to the laser depletion length. With a 200 TW laser pulse, this results in an x-ray beam with a median photon energy of 20 keV, >6×108  photons above 1 keV per shot, and a peak brightness of 3×1022  photons s−1 mrad−2 mm−2 (0.1%  BW)−1.